Impact of lignans in oilseed mix on gut microbiome composition and enterolignan production in younger healthy and premenopausal women: an in vitro pilot study - Corona, Giulia (Microb Cell Fact, 2020)
BACKGROUND: Dietary lignans belong to the group of phytoestrogens together with coumestans, stilbenes and isoflavones, and themselves do not exhibit oestrogen-like properties. Nonetheless, the gut microbiota converts them into enterolignans, which show chemical similarity to the human oestrogen molecule. One of the richest dietary sources of lignans are oilseeds, including flaxseed. The aim of this pilot study was to determine the concentration of the main dietary lignans in an oilseed mix, and explore the gut microbiota-dependent production of enterolignans for oestrogen substitution in young and premenopausal women. The oilseed mix was fermented in a pH-controlled batch culture system inoculated with women’s faecal samples. The lignan content and enterolignan production were measured by ultra‐high-performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS), and the faecal-derived microbial communities were profiled by 16S rRNA gene-based next-generation sequencing. RESULTS: In vitro batch culture fermentation of faecal samples inoculated with oilseed mix for 24 h resulted in a substantial increase in enterolactone production in younger women and an increase in enterodiol in the premenopausal group. As for the gut microbiota, different baseline profiles were observed as well as different temporal dynamics, mainly related to Clostridiaceae, and Klebsiella and Collinsella spp. CONCLUSIONS: Despite the small sample size, our pilot study revealed that lignan-rich oilseeds could strongly influence the faecal microbiota of both younger and premenopausal females, leading to a different enterolignan profile being produced. Further studies in larger cohorts are needed to evaluate the long-term effects of lignan-rich diets on the gut microbiota and find out how enterolactone-producing bacterial species could be increased. Diets rich in lignans could potentially serve as a safe supplement of oestrogen analogues to meet the cellular needs of endogenous oestrogen and deliver numerous health benefits, provided that the premenopausal woman microbiota is capable of converting dietary precursors into enterolignans. [Image: see text]